The Influence of Compensation and Motivation on Gen Z's Work Interests - Destiny, Sanjung Nevi; Sidi, Agus Purnomo (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2025)
The large number of unemployment and turnover rates in Gen Z is a problem for a company. For this reason, it is necessary to conduct a study to determine the factors that influence Gen Z's job interest in Malang. This study used accidental sampling which amounted to 115 people. This research uses a quantitative approach by utilizing multiple regression SPSS analysis tools. The results of this study indicate that simultaneously compensation and motivation have a significant effect on Gen Z's job interest. Partially, compensation has not a significant effect on Gen Z work interest. Motivation has a significant effect on Gen Z job interest. The company is advised to prioritize strategies that can enhance the motivation of Gen Z. Although compensation does not show a significant partial effect, the average compensation value remains fairly high. Therefore, the company must continue to maintain a fair and competitive compensation system so that Gen Z feels valued and recognized.